An analytical framework to review judicial decisions based on the precautionary principle with a case-study application - Gonçalves, V. (2019)
The precautionary principle has been applied in environmental policy and law internationally in the assessment and management of uncertain risks. Different legal roles in different jurisdictions have depended on legal cultures and also on political, economic and environmental contexts. At the level of individual jurisdictions the application of the principle has shown some ambiguity in the interpretation of the concept of precaution, insufficient knowledge of the potential impacts and lack of operational frameworks to support decisions. This has hindered the functioning of administrative justice and generated discretion and unpredictability in the decision process. This article intends to develop a systematic analysis of legal proceedings in a national jurisdiction in order to clarify how the precautionary principle has been interpreted and applied by the courts in the analysis of conflicts associated with serious risks to the environment and to public health. It is also intended to contribute to the debate on when and how to apply precautionary measures. In order to evaluate the degree of consistency of the courts’ decisions in relation to comparable risks and their proportionality with respect to the severity of hazards, a theoretical framework was developed based on three attributes: level of seriousness of hazards, level of evidence required, level of severity of precautionary measures. A case-study application of this framework was developed for Portuguese courts. The judicial cases where the precautionary principle was invoked between 2007 and 2014 were considered, in the areas of waste incineration, high voltage power lines, dam and wind farm construction. Different positions among courts were observed, with contradictory arguments in the same case or in similar cases. In order to counteract this, more explicit legal requirements and criteria for the analysis of uncertain risks and the weighting of interests by area of activity are proposed.